Quantifying Quantum Correlation of Quasi‐Werner State and Probing Its Suitability for Quantum Teleportation (Ann. Phys. 10/2021). Issue 10 (18th October 2021) - Chatterjee, Arpita; Thapliyal, Kishore; Pathak, Anirban
Abstract : Quantum Correlations In article number 2100201, Arpita Chatterjee, Kishore Thapliyal, and Anirban Pathak establish the relevance of photon addition in the enhancement of single‐ and two‐mode (bipartite correlations) nonclassical properties and teleportation performance using the Wigner function, entanglement, and discord of the two‐mode quasi‐Werner state. Efficacy of photon addition in the entanglement distillation is also established.